Optimization of Lipase‐Catalyzed Interesterification of Flaxseed Oil and Tricaprylin Using Response Surface Methodology. (13th November 2013) - Khodadadi, Maryam; Kermasha, Selim
Abstract: The biosynthesis of structured lipids (SL) in organic solvent media was carried out by the interesterification of flaxseed oil (FO) and tricaprylin (TC), using Novozym 435. The bioconversion yield (BY, %) of medium‐long‐medium type SL, including C‐caprylic and Ln‐linolenic acids (CLnC), La‐linoleic acid (CLaC) and O‐oleic acid (COC), was monitored. Response surface methodology was used to obtain significant models for the responses, on the basis of a five level, five variable central composite rotatable design. In the experimental preliminary trials significant reaction parameters, including reaction temperature ( T r ), TC/FO molar ratio ( M r ), enzyme concentration ( E c ), reaction time ( R t ) and initial water activity ( a w ), were considered for optimization. Significant models for CLnC, CLaC and COC were determined after regression analysis with backward elimination. The optimal conditions, generated for a maximum CLnC, CLaC and COC, were found to be 54.50–56.25 °C for T r, 6.23–6.25 mol/mol for M r, 2.68–3.13 % for E c, 36.58–37.50 h for R t and 0.15–0.33 for a w . Under these optimum conditions, the BY of CLnC, CLaC and COC was predicted to be 32.48–36.67, 3.26–3.38 and 5.79–6.16 %, respectively.